2015
DOI: 10.1002/jsc.2000
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition and Outreach Performance of Microfinance Institutions: Evidence from East Africa

Abstract: Past research suggests that board decisions have an impact on the (broadly defi ned) performance and/or mission of organizations ( Zahra et al ., 2009 ;Milana and Ashta, 2012 ). Furthermore, the signifi cant interest in board issues within both academic and policy circles is partly driven by the fact that board decisions and board behavior are believed to be aff ected by board composition and board diversity (e.g., Van Ees et al ., 2009 ). In the academic literature, a large number of studies have analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 57 publications
8
53
1
Order By: Relevance
“…However, the institutions are not profitable as the average ROA is negative (85%). Mori et al (2015) observed similar negative returns on assets for MFIs in East Africa. This could be because of the diverse nature of the industry as most MFIs in SSA are made up of cooperatives and NGOs with dominant social performance goals.…”
Section: Empirical Results and Discussionmentioning
confidence: 59%
“…However, the institutions are not profitable as the average ROA is negative (85%). Mori et al (2015) observed similar negative returns on assets for MFIs in East Africa. This could be because of the diverse nature of the industry as most MFIs in SSA are made up of cooperatives and NGOs with dominant social performance goals.…”
Section: Empirical Results and Discussionmentioning
confidence: 59%
“…However, unlike Hudon (2010), we control for selection bias, given that only MFIs that decide to be rated by Planet Rating can obtain a governance score. Third, by linking governance quality to MFI outreach performance, we also extend Hudon (2010) and previous studies that relate individual governance mechanism to MFI social performance (Hartarska, 2005;Mersland & Strøm, 2009;Mori et al, 2015;Tchakoute Tchuigoua, 2011). Findings obtained after controlling for selection bias suggest that board expertise, board activity, and ownership type are the main board characteristics that significantly determine the quality of MFI governance.…”
Section: Introductionsupporting
confidence: 54%
“…Mersland and Strøm (2009) find that CEO-chairman duality is positively associated with MFI outreach. Mori et al (2015) study a sample of East Africa MFIs and find MFIs with more independent and more international board members have better outreach performance. Except for CEO-chairman duality, international board members, and independent directors, other individual governance mechanisms are irrelevant in explaining MFI social outreach.…”
Section: Governance Quality and Mfi Outreachmentioning
confidence: 99%
See 2 more Smart Citations